A study of antibiotic agents prescribed, guideline compliance and associated factor of antibiotic failure among the hospitalised paediatric and adult general medical patients in Hospital Universiti Sains Malaysia - Ramli, Nurshahira (2023)
Background: Antibiotic is the commonest drugs used in hospitals. Inappropriate use of antibiotics has been shown to contribute to the occurrence of multidrug-resistant organisms (MROs). Understanding antibiotic prescription patterns is essential for combatting limited access and excessive use of antibiotics and controlling resistance. Thus, we evaluated antibiotic agents prescribed and the associated factor of antibiotic failure among hospitalized adult and pediatric patients in Hospital USM. Methodology: This was a retrospective study of antibiotic patterns among the adult general and pediatric general medical wards. A total of 227 patients were identified after had fulfilled the inclusion and exclusion criteria. This study used descriptive and inferential analysis to find out the objectives. The descriptive analysis includes the frequencies, percentage, mean and standard deviation, carried out to determine the patient’s demographic, patient’s clinical diagnosis, and patients comorbid. The inferential statistics involving simple logistic and multiple logistic regression are conducted to identify the factors associated with antibiotics failure. Results: Respiratory tract infections were found to be the highest infection sites and treated with antibiotics among all age groups with a total of 163 patients. Among these, 57.7% (94 patients) have been prescribed with penicillin with β-lactamase inhibitor group, followed by 28.8% (47 patients) with macrolide and a balance of 13.5% with other groups. Amoxicillin and clavulanic acid were reported to be the commonest among the penicillin with β-lactamase inhibitor group prescribed which was 65.2%. A total of 160 (70.5%) patients' prescription was noted as a single prescription while only 67 (29.5%) were of 2 antibiotics combination prescription. Most of them were given parenterally(75.3%). As of notes, more than half of prescriptions 60.8% (138) were deemed compliance to the guidelines. The rate of antibiotic failure was 12.8% (29) which was quite similar to a few other studies. 3 factors that been identified as the significant associated factor of antibiotic failure in this study were female sex (OR, 3.459; 95% CI, 1.075,11.130), the presence of acute kidney injury (OR, 3.084; 95% CI, 1.021, 9.311) and resistant organisms (OR, 2.961; 95% CI, 3.813,97.916). Conclusion: Most of the antibiotics prescribed in this study were penicillin with β-lactamase inhibitors. Despite this, there was only 12.8% (29) antibiotic failure and only 3 significant associated factors of failure were reported. Further larger scale and longer study needed to look for more antibiotic prescriptions not limited to the medical ward but including all disciplines such as surgical, orthopaedic, obstetrics, and gynaecology to conclude more realistic rate of antibiotic failure and associated factors.